FENOMENA PHUBBING PADA JEMAAH MASJID RAYA TELUK KUANTAN KABUPATEN KUANTAN SINGINGI - Aprilianti, Welly; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Phubbing comes from a combination of the terms telephone and snubbing, which is interpreted as an attitude of ignoring the person you are talking to by using a smartphone excessively. The phenomenon of phubbing at the Teluk Kuantan Grand Mosque occurs during recitation where the lecturer is delivering tausiyah but the congregation's attention is more focused on smartphones and this research aims to find out what the motive is for someone to do phubbing and find out what the meaning of phubbing is for phubbers and phubbing victims in interpreting phubbing behavior. This research uses a qualitative method with a phenomenological approach. The informants used in this research were 7 congregation members and 2 lecturers who were taken based on accidental techniques. Data collection techniques in this research took the form of in-depth interviews, observation and documentation. For data analysis techniques the author uses data reduction, data presentation and drawing conclusions. To describe the research results in checking the validity of the data, the author uses triangulation techniques, credibility, extended observations, uses reference materials and conducts member checks. The results of this research show that the motives for phubbing behavior of the congregation at the Teluk Kuantan Grand Mosque are divided into cause and purpose motives. The reason the congregation does phubbing (because of motive) is feeling bored, people around doing phubbing, smartphone addiction and Fomo. Meanwhile, the motive in the future or the goal that a person wants to achieve in carrying out a certain action (in order motive) is to seek pleasure (entertainment) and seek information. In its meaning, the meaning of the congregation regarding the phubbing phenomenon is defined as negative behavior, where a person's behavior who is more focused on his smartphone makes it seem like he doesn't care about his surroundings and ignores other people. Along with increasingly sophisticated technological developments, phubbing behavior is considered a normal phenomenon for both phubbers and phubbing victims. However, phubbing behavior often offends the feelings of the person you are talking to. This is because the interlocutor feels unappreciated when the phubber focuses on his smartphone and tends to ignore direct communication with the interlocutor who is the victim of phubbing. Keywords: Phenomenology, Phubbing, Smartphone, Motif and Meaning.